Memory T-cells and characterization of peripheral T-cell clones in acute Kawasaki disease - Franco, Alessandra; Shimizu, Chisato; Tremoulet, Adriana H.; Burns, Jane C. (Autoimmunity (Chur, Switzerland), 2010)
Kawasaki disease (KD) is a pediatric self-limited vasculitis characterized by immune-mediated destruction of the arterial wall and myocardium. Neither the trigger that incites the inflammation nor the switch that turns it off is known. To further our understanding of KD pathogenesis and the role of regulatory T-cells in modulating the inflammatory response, we studied circulating effector memory T-cells (CCR7 − and IL-15+ Tem) and central memory T-cells (CCR7+ and IL-15+ Tcm) in six KD subjects. In two of the subjects, we cloned the remaining T-cell population by limiting dilution. TaqMan analysis of Tem studied in two KD subjects suggested that Tem are pro-inflammatory CD4+T-helper 1 cells and CD8+ cytotoxic T-cells. Following memory T-cells over time, we defined that circulating Tem and Tcm are detectable during the acute phase in some KD subjects before treatment with intravenous immunoglobulin. Both Tem and Tcm expand rapidly within 2 weeks of treatment. The circulating Tem pool contracts, while Tcm further proliferate in the convalescent phase. Following depletion of memory T-cells, numerous T-cell clones were derived from two acute KD subjects. The large majority of these T-cells displayed the functional phenotype of peripherally induced regulatory T-cells (Treg). These findings provide insight into the nature and kinetics of the adaptive immune response in KD.